Termination of Pregnancy in Mismated Bitches using Cloprostenol and Cabergoline - Parmar, Bhanusinh M.; Panchal, Mahesh T.; Chaudhari, Dinesh V.; Damor, Kantibhai M. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Bitches (n=6) having unwanted pregnancy were subjected to termination using combination of cloprostenol and cabergoline after  scanning using ultrasound on day 30-35 post-mating. The bitches were treated with a combination of Inj. Cloprostenol (@ 2 µg/kg b. wt.,  s/c) and Tab. Cabergoline (@ 5 µg/kg b. wt., orally) once a day, for 3 to 4 consecutive days, and were observed for onset and completion  of abortion. All the bitches aborted safely with 3 to 4 treatments with a litter size of 2 to 7 puppies. The mean induction time for abortion  was 81.38±3.88 hrs and the mean total duration of whelping was 13.17±2.95 hrs, with milder side effects, viz., crying, vomiting, anorexia  and tachypnea without future complications. An ultrasonographic scan was made in each of the bitch after termination of pregnancy  and again on day 70 to 100 post-treatment to rule out the retained fetal pups and complications like pyometra or maceration, if any,  respectively. None of the bitches had retained pup and had no any complication during the follow up period. The mean values of  haemoglobin, WBCs and RBCs counts between pre- and post-treatment (on day 0 and 7/8) periods were also similar in bitches. The  combination of Inj. Cloprostenol) and Tab. Cabergoline terminated the unwanted canine pregnancies after 30 to 35 days post-mating  within 3 to 4 days, with milder side effects amenable to medications.
Keywords: Bitch; Cloprostenol; Cabergoline; Misalliance; Termination of pregnancy; Side effects